Histological regression of peritoneal metastases of recurrent tubo-ovarian cancer after systemic chemotherapy - Pache, Basile; Teixeira Farinha, Hugo; Toussaint, Laura; Demartines, Nicolas; Hastir, Delfyne; Mathevet, Patrice; Sempoux, Christine; Hübner, Martin (Frontiers in Surgery, 2022)
Introduction : Post-treatment histological regression of peritoneal metastases (PM) is a new and potentially important predictor of oncological outcomes. Histology of PM from adnexal origin is usually evaluated by Chemotherapy Response Score (CRS). The aim of this study was to quantify response of PM of recurrent tubo-ovarian cancer (TOVC) after systemic chemotherapy by using the recently validated Peritoneal Regression Grading System (PRGS) and compare it with CRS. Correlation with per operative evaluation through Peritoneal Carcinose Index (PCI) was performed. Material and methods : Retrospective cohort study of all consecutive patients with recurrent PM from TOVC undergoing surgery after prior systemic chemotherapy from January 2015 to March 2019. Biopsies were assessed with the 4-scale PRGS. Results : Thirty-eight patients were included. Patients had a median of 2 (range 1-2) lines and 12 (range 3-18) cycles of prior systemic chemotherapy. Overall mean (SD) PRGS was 2.3 (± 1.1). 26 % (10) of patients had complete response (PRGS 1), 40% (15) had major response (PRGS 2), 26 % (10) minor response (PRGS 3) and 8% (3) had no response (PRGS 4). Mean PRGS was positively correlated to Peritoneal Cancer Index (PCI) (ϱ= 0.5302, p=0. 0003), and inversely with CRS (ϱ= -0.8403, p<0.0001). No correlation was highlighted between mean PRGS and overall survival (ϱ= -0.0195, p=0.9073). Conclusion : CRS and mean PRGS correlated to each other. Histological response of PM after systemic chemotherapy was quantifiable and variable. The role of PRGS for the evaluation of treatment response and as potential surrogate marker for oncological outcomes is part of ongoing and planned research.